LINTASAN BASAH MELALUI DASAR SUNGAI UNTUK LALU LINTAS KENDARAAN - Lanneke Tristanto; Setyo Hardono; Rully Ranastra (Jurnal Jalan-Jembatan, 2009)
Fords are frequently regarded as temporary crossings as it is expected that they will be replaced by permanent bridging in the near future. However, a properly constructed ford will be more effective than a poorly built bridge due to lack of funding. The main criterion for ford design is the vertical alignment to meet the required safety and comfort in vehicle riding quality. Fords are most suitable for wide rivers with short flooding periods. This paper describes the principals for design and construction of gabion and concrete ford types. The case study evaluation of an actual ford construction compared to the costs of a semi-permanent Bailey bridge and cable-stayed foot-bridge, reveals that the gabion ford is the most economical and efficient solution. Key words : ford/weir/dip, vertical alignment, gabion, gabion ford, concrete ford